Analisis Faktor-Faktor yang Berpengaruh Terhadap Cash Holdings - Yanti, Merry Ira; Wati, Erna (Global Financial Accounting Journal, 2018)
This research examines factors that have impact on determination of cash holdings in companies listed in Indonesian Stock Exchange. The sample of this research is 328 nonfinancial companies listed in Indonesian Stock Exchange period 2012 until 2016. The sampling method used was purposive sampling. The result shows that cash flow, cash flow volatility, and dividend have positive significant effect on corporate cash holding. Leverage, liquidity, profitability have significant negative effect on corporate cash holding. Debt structure, firm size, and growth opportunityhave insignificant on corporate cash holdings.